Fair Progress? : Economic Mobility Across Generations Around the World - Narayan, Ambar; Van der Weide, Roy; Cojocaru, Alexandru; Lakner, Christoph; Redaelli, Silvia; Mahler, Daniel Gerszon; Ramasubbaiah, Rakesh Gupta N.; Thewissen, Stefan (Washington, DC: World Bank, 2017)
Fair Progress? Economic Mobility Across Generations Around the World looks at an issue that has gotten much attention in the developed world, but with, for the first time, new data and analysis covering most of the world, including developing economies. The analysis examines whether those born in poverty or in prosperity are destined to remain in the same economic circumstances into which they were born, and looks back over a half a century at whether children’s lives are better or worse than their parents’ in different parts of the world. It suggests local, national, and global actions and policies that can help break the cycle of poverty, paving the way for the next generation to realize their potential and improve their lives.